PENGARUH ASPEK PENGGUNAAN TENAGA KERJA DAN IZIN KERJA BAGI PENGGUNAAN TENAGA KERJA ASING TERHADAP KEGIATAN PENANAMAN MODAL DI INDONESIA - I ketut astawa; Daud Munasto (Universitas Labuhanbatu, 2021)
Employment problems can arise due to several factors such as education, job opportunities and relatively low economic growth. This is experienced by many countries including Indonesia. This writing aims to determine the effect of aspects of the use of labor and work permits for the use of foreign workers on investment activities in Indonesia. The writing method used in this paper is a literature review method (library research). From the discussion, it can be concluded that the employment issue is a very important element to get the attention of all parties related to foreign workers, because the impact it can have can encourage an increase in foreign investment in Indonesia on investment. Aspects of the Obligation to Use Indonesian Workers and the Obligation to Organize Industrial Training (Industrial Training) and Work Permits for the Use of Foreign Workers (TKA) on Investment Activities in Indonesia have a major influence on investment activities in Indonesia. For this reason, labor regulations must be supported by adequate laws and regulations according to the demands of the interests of the community and investment actors in Indonesia.Keywords: influence, employment, investment, investment